(untitled) (Kairaranga, 2022)
How well classmates communicate support with each other may significantly influence how well they learn and their commitment to learning. This study asked students which aspects of supportive communication they use with each other and which aspects they regard as most important for successful study. One hundred polytechnic students participated in this study. They rated how frequently they experienced and how influential they considered 18 aspects of supportive communication between classmates for study success. The students regarded many aspects of supportive communication influential but few aspects were present in most instances. They experienced and valued able and motivated supporters, and supportive relationships with classmates the most. Students in similar years of study experienced and valued similar aspects of supportive communication. Training a whole class in supportive communication may develop positive shared values among the students and a climate that encourages mutual support. Courses that provide ongoing activities and opportunities for students to develop their skills in communicating support may produce more successful students.